Revitalization of Organization and Business Determination of BUMDes Cibadak Mandiri of Cibadak Village, Ciampea District, Bogor Regency - Mokhamad Syaefudin Andrianto; Rindang Matoati; Wita Juwita Ermawati (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
BUMDes Cibadak Mandiri has stopped operating, so to revive it, it must be replaced by new management. The new management seeks a partner to restore and run the business. The